SIGNIFIKANSI NILAI PERUSAHAAN MELALUI VARIABEL INTELLECTUAL CAPITAL DAN KINERJA KEUANGAN PADA PERUSAHAAN INDEKS LQ45 - Fajrul Rahman Bayau; Abdul Hadi Sirat; Hartaty Hadady (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2021)
Objective: This study aims to determine the significance of the firm value through the variable Intellectual capital and financial performance as an intervening variable in LQ45 companies listed in Indonesia Stock Exchange, with a sample of 20 companies.Methodology: The analytical method used is path analysis. The observation time was 5 years and the research data is secondary data by using purposive sampling method. In this research, intellectual capital is measured with a VAIC, financial performance measured by ROA, and the company's value is measured by Tobin's Q.Finding: Ha1, Ha2, and Ha3 are rejected, at the 5% confidence level.Conclusion: The results of this study indicate that intellectual capital has a positive effect on the financial performance, financial performance has a positive effect on corporate value, intellectual capital directly positive effect on the firm value, and financial performance is able to mediate the relations of intellectual capital on firm value even if the direct effect is greater than the indirect effect.